Gastrointestinal Motility, Mucosal Mast Cell, and Intestinal Histology in Rats: Effect of Prednisone - De Lima, Maysa Bruno; Gama, Loyane Almeida [UNESP]; Hauschildt, Andrieli Taise; Dall'Agnol, Denize Jussara Rupolo [UNESP]; Corá, Luciana Aparecida; Americo, Madileine Francely (Wiley, 2017)
Our aim was to verify the effects of prednisone related to gastrointestinal motility, intestinal histology, and mucosal mast cells in rats. Two-month-old male Wistar rats were randomly assigned to control group (vehicle) animals receiving saline 0.9% (n=7) or treated orally with 0.625 mg/kg/day of prednisone (n=7) or 2.5 mg/kg/day of prednisone (n=7) during 15 days. Mast cells and other histologic analyses were performed in order to correlate to gastric emptying, cecum arrival, and small intestine transit evaluated by Alternating Current Biosusceptometry. Results showed that prednisone in adult rats increased the frequency of gastric contractions, hastened gastric emptying, slowed small intestinal transit, and reduced mucosal mast cells. Histologically, the treatment with both doses of prednisone decreased villus height, whereas longitudinal and circular muscles and crypt depth were not affected. These findings indicate an impairment of intestinal absorption which may be linked to several GI dysfunctions and symptoms. The relationship between gastrointestinal motor disorders and cellular immunity needs to be clarified in experimental studies since prednisone is one of the most prescribed glucocorticoids worldwide.